A STUDY OF LEVELS OF hs-CRP AND LIPID PROFILE IN PATIENTS WITH DIABETIC NEPHROPATHY (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: Diabetes mellitus (DM), which has a high morbidity and mortality rate, has emerged as a significant worldwide health issue. One of the most significant long-term microvascular consequences of diabetes mellitus (DM) is type 2 diabetic nephropathy (T2DN), which is a major contributor to end-stage renal disease (ESRD) globally. There is data indicating that T2DM is a mild inflammatory condition. Inflammatory markers including high-sensitivity C-reactive protein (hs-CRP) have been linked to an increased risk of diabetes, and its role in diabetic nephropathy (DN) pathogenesis is yet unknown. AIM: This study aimed to measure the levels of serum high sensitivity C-reactive protein(hs- CRP) and lipid profile in patients with diabetic nephropathy and to compare with that of normal subjects. MATERIAL AND METHODS: In this study, T2DM patients with nephropathy were enrolled in the study group (n=70) and healthy subjects were enrolled in the control group (n=70). Serum hs-CRP levels and lipid profile were assessed in both the groups. The data was analysed using SPSS version 26. RESULTS: When compared to controls, patients with DN had significantly higher levels of hs-CRP as compared to that of controls. The mean value total cholesterol, LDL, and triglycerides is also significantly more in patients with diabetic nephropathy as compared to controls with p-value <0.001. CONCLUSION: According to our findings, patients with diabetic nephropathy frequently experience an increase in hs-CRP levels along with dyslipidemia. Regular monitoring of these markers may help to reduce the incidence of unfavourable outcomes in patients with diabetic nephropathy.